Characterization of an Alteromonas long-type ulvan lyase involved in the degradation of ulvan extracted from Ulva ohnoi. Issue 11 (2nd November 2017) - He, Chuan; Muramatsu, Hisashi; Kato, Shin-ichiro; Ohnishi, Kouhei
Abstract: Ulvan is a sulfated polysaccharide found in the cell wall of the green algae Ulva . We first isolated several ulvan-utilizing Alteromonas sp. from the feces of small marine animals. The strain with the highest ulvan-degrading activity, KUL17, was analyzed further. We identified a 55-kDa ulvan-degrading protein secreted by this strain and cloned the gene encoding for it. The deduced amino acid sequence indicated that the enzyme belongs to polysaccharide lyase family 24 and thus the protein was named ulvan lyase. The predicted molecular mass of this enzyme is 110 kDa, which is different from that of the identified protein. By deletion analysis, the catalytic domain was proven to be located on the N-terminal half of the protein. KUL17 contains two ulvan lyases, one long and one short, but the secreted and cleaved long ulvan lyase was demonstrated to be the major enzyme for ulvan degradation. Abstract: : (A) Domain structure of UllAKUL17 and plasmids containing UllAKUL17 . (B) CBB R-250 staining of 10% SDS-PAGE gel. (C) Activity staining with ulvan-containing agarose gel.